Implementation of Talaqqi Method in Memorizing Al-Qur'an at School of Hafidz Qur'an of Muhajirin in Central Gresik - Hanif Ashar (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
The formulation of this research problem is: first, how is the implementation of Talaqqi method in memorizing Al Qur'an at School of Hafidz Qur'an of Muhajirin in Central Gresik ?; second, what are the inhibiting and its supporting factors?; third, how is the solution to overcome these obstacles?The type of research in this study used field research with a qualitative approach; and the methods of data collection were observation, interviews, and documentation.The research findings in this research can be concluded that first: The implementation of Talaqqi method in memorizing Al Qur'an at School of Hafidz Qur'an of Muhajirin in Central Gresik is carried out with four stages: preparation, applying, material, evaluation and closing; second: supporting factor of talaqqi method implementation in memorizing Al-Qur'an at School of Hafidz Qur'an of Muhajirin in Central Gresik that is the existence of adequate facilities, productivity of santri (students)’ age, professionalism of teachers based on the fields, treatment of ustadz/ustadzah (teachers), quiet environment, santri guardian, as well as regular meetings. While, the inhibiting factors are santri’s difficulty in arranging time, lack of awareness of talaqqi method benefit, lack of santri’s fluency in reading Al-Qur'an, and lack of santri guardian’s support; third: the solution to overcome these obstacles is to give the task of memorizing at home, to provide a model of tadarrus (reciting) the Qur'an, to encourage students to study in the TPQ (a place of learning to recite Al-Qur'an), to establish communication with the santri guardian. Keywords: Talaqqi Method, Memorizing Al Qur'an, Implementation